2021
DOI: 10.3390/v13020237
|View full text |Cite
|
Sign up to set email alerts
|

A Crucial Role of ACBD3 Required for Coxsackievirus Infection in Animal Model Developed by AAV-Mediated CRISPR Genome Editing Technique

Abstract: Genetic screens using CRISPR/Cas9 have been exploited to discover host–virus interactions. These screens have identified viral dependencies on host proteins during their life cycle and potential antiviral strategies. The acyl-CoA binding domain containing 3 (ACBD3) was identified as an essential host factor for the Coxsackievirus B3 (CVB3) infection. Other groups have also investigated the role of ACBD3 as a host factor for diverse enteroviruses in cultured cells. However, it has not been tested if ACBD3 is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Recently, a genome-wide screen using CRISPR/Cas9 was conducted to identify host factors that may potentially participate in the replication of certain viruses, such as SARS-CoV-2 ( 90 ), HIV ( 91 ), arthritic alphaviruses ( 92 ), Coxsackie virus ( 93 ), Venezuelan equine encephalitis virus (VEEV) ( 94 ) and influenza virus ( 95 ). For the influenza virus, it was demonstrated that inactivation of specific host genes, such as DOCK5, Annexin-A1, IFIT2, IRF7 and ZDHHC22, can induce protection against cell death during infection ( 96 100 ).…”
Section: Crispr-cas9 Applicationsmentioning
confidence: 99%
“…Recently, a genome-wide screen using CRISPR/Cas9 was conducted to identify host factors that may potentially participate in the replication of certain viruses, such as SARS-CoV-2 ( 90 ), HIV ( 91 ), arthritic alphaviruses ( 92 ), Coxsackie virus ( 93 ), Venezuelan equine encephalitis virus (VEEV) ( 94 ) and influenza virus ( 95 ). For the influenza virus, it was demonstrated that inactivation of specific host genes, such as DOCK5, Annexin-A1, IFIT2, IRF7 and ZDHHC22, can induce protection against cell death during infection ( 96 100 ).…”
Section: Crispr-cas9 Applicationsmentioning
confidence: 99%
“…Recently, genome-wide CRISPR/Cas9 screening has been used to identify host factors that are potentially involved in the replications of some viruses, such as the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ 96 ], HIV [ 97 ], arthritogenic alphaviruses [ 98 ], Coxsackievirus [ 99 ], Venezuelan equine encephalitis virus (VEEV) [ 100 ], and influenza virus [ 101 ]. For the influenza virus, it has been demonstrated that inactivation of the specific host genes, such as DOCK5, Annexin-A1, IFIT2, IRF7, and ZDHHC22, can induce protection against cell death by influenza virus infection [ 102 , 103 , 104 , 105 , 106 ].…”
Section: Crispr/cas System In Virology Researchmentioning
confidence: 99%